The use of systemic medications in pediatric dermatoses: A review - Narla, Shanthi; Rahmayunita, Githa; Astriningrum, Rinadewi; Shwayder, Tor; Yosi, Ariyati; Lim, Henry W. (UI Scholars Hub, 2019)
Research has begun to illustrate a favorable efficacy and side-effect profile for many systemic agents used in pediatric dermatological conditions (i.e. atopic dermatitis, psoriasis, scleroderma, alopecia areata, chronic spontaneous urticaria, autoimmune blistering disorders, and hidradenitis suppurativa) despite not having extensive randomized clinical trials. The purpose of this article is to summarize the available data on the treatment regiments, safety, and efficacy of systemic immunosuppressants, including the newer biologics, focusing on the most up-to-date systematic reviews or randomized clinical trials. The review demonstrates that many of the present studies lack data on long-term efficacy and consist of small patient populations. Further research into the long-term safety of these systemic medications is of vital importance especially due to the chronic nature of most pediatric dermatological conditions that require the use of systemic agents.